In silico identification of human microRNAs pointing centrin genes in Leishmania donovani: Considering the RNAi-mediated gene control - Aljedaie, Manei M.; Alam, Pravej (Frontiers in Genetics, 2024)
Purpose: Leishmaniasis, caused by different species of the protozoa parasite Leishmania is a neglected tropical human disease and is endemic in about a hundred countries across the globe. According to the World Health Organization (WHO), the annual incidence of cutaneous leishmaniasis is estimated to be 0.7 to 1.2 million cases globally, while the annual incidence of visceral leishmaniasis is estimated to be 0.2 to 0.4 million cases. In many eukaryotic organisms, including human beings and protozoan parasites, centrin genes encode proteins that play essential roles within the centrosome or basal body. Proteins encoded by centrin genes play essential roles in the centrosome or basal body of several eukaryotes, including protozoan parasites and Homo sapiens (humans). The human miRNAs have been related to several infectious and non-infectious diseases associated with pathogen-host interactions, and they play the emphatic roles of gene expression regulators.Methods: In this study, we employed the MirTarget bioinformatics tool, a machine learningbased approach implemented in miRDB, to predict the target of human miRNAs in centrin genes of L. donovani. For cross-validation, we utilized additional prediction algorithms, namely RNA22 and RNAhybrid, targeting all five centrin isotypes.In this study, the target of human miRNAs in centrin genes of L. donovani was predicted by employing a machine learning (ML) based MirTarget bioinformatics tool implemented in miRDB. Other prediction algorithms-RNA22, and RNAhybrid, were also employed for cross-validation of predicted miRNAs through miRDB targeting all five centrin isotypes.Results: The centrin-3 (LDBPK_342160) and putative centrin-5 (NC_018236.1) genes in L.donovani were targeted by eight and twelve human miRNAs, respectively, among 2635 known miRNAs (miRbase). Hsa-miR-5193 consistently targeted both genes... hsa-miR-5193 was the only human miRNA found unanimously targeting centrin3 and centrin5 genes. Also, their targets and off-targets in human homologs of centrin, inflammation, and immune-responsive genes were predicted through TargetScan, Tarbase, miRecords, miRTarbase database searching. The biological roles of human miRNAs, as a major gene regulator during pathogen-host interactions predicted by in silico tools help in the exploration of a regulatory pattern of human miRNAs in an early phase of inflammatory response.